Studies on the transmission of malignant catarrhal fever in experimental animals: Bali cattle in close contact with sheep - Agus Wiyono; Rini Damayanti (Indonesian Center for Animal Research and Development (ICARD), 1999)
pregnant sheep and lambing sheep were conducted in two different periods and flocks of Bali cattle and sheep. On the basis of clinico-pathological findings and polymerase chain reaction (PCR) tests, the study revealed that MCF transmission has been successfully achieved in four Bali cattle that were in contact with lambing sheep, and in one Bali cow that was penned 100 metres away from lambing sheep pen. The polymerase chain reaction (PCR) detected the causal agent of MCF in peripheral blood leucocytes (PBL) and nasal, ocular and vaginal secretions of sheep. It is assumed that viruses in the secretion were spread by sheep causing five Bali cattle suffered with MCF. However, further studies on exact mode of transmission needs to be clarified particularly on the time and mode of viral transmission from reservoir to susceptible animals. Key words : Malignant catarrhal fever, experimental transmission, in-contact, Bali cattle, sheep